2019
DOI: 10.3390/rs11232830
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Post-Earthquake Damaged Building with Interferometric Real Aperture Radar

Abstract: In this study the main results of a detailed analysis of an actual building, which was severely damaged during the Mw 5.1, May 11th 2011, Lorca earthquake (Murcia, Spain) are presented. The dynamic behavior of the building was analyzed by means of empirical and numerical approaches. The displacement response of the building submitted to ambient noise was recorded by using a Real Aperture Radar (RAR). This approach provides a secure remote sensing procedure that does not require entering the building. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The sampling parameters can be adjusted with the provided software. More details on the use and specifications of the RAR used in this study can be found in [13,14].…”
Section: The Real-aperture Radar (Rar)mentioning
confidence: 99%
See 3 more Smart Citations
“…The sampling parameters can be adjusted with the provided software. More details on the use and specifications of the RAR used in this study can be found in [13,14].…”
Section: The Real-aperture Radar (Rar)mentioning
confidence: 99%
“…A detailed description of the working principle of the RAR can be found in [13,14]. One main feature of the radar is that it can simultaneously capture the movement of different objects that are in the field of view (FOV) of the RAR antenna.…”
Section: Rar Interferometrymentioning
confidence: 99%
See 2 more Smart Citations
“…This paper aims to identify state-of-the-art data sources for building damage assessment and serve as a guide to make more efficient data collection based on the experiences in the last years. Damage is understood as a change in the mechanical, material and/or geometric properties of a building, affecting its performance and behaviour [8]. Damage data is highly 'perishable' or ephemeral since damaged structures may be altered or removed during rescue or early recovery [9] activities [10] or modified by aftershocks.…”
Section: Introductionmentioning
confidence: 99%